PENERAPAN SISTEM PENDUKUNG KEPUTUSAN DENGAN METODE AHP UNTUK PENILAIAN KARYAWAN TERBAIK - Ellanda Purwawijaya (LPPM Politeknik LP3I Medan, 2020)
Employees are one of the most important assets owned by a company in its business maintain survival, develop, the ability to compete and earn a profit. Competition in the increasingly competitive business world has spurred companies to strive harder improve the quality of the company. One of the efforts is to improve the quality of resources humans because the quality of good human resources can increase productivity and achievement a company. In order for the quality of employees to be maintained and improved, the company needs to do something employee performance appraisal in the form of determining the best employee. There are several criteria that will be applied several companies in assessing the best employees, but the criteria still vary. This study will discuss the assessment of the best employees by applying seven criteria. seventh These criteria are quality of work, quantity of work, speed of work, mastery of the field, discipline, Initiative, and loyalty. Data analysis using AHP (Analytical Hierarchy process) method. allows mathematical calculations with various criteria. The application will be designed based on website and data to be stored using the mysql database.